Late Cretaceous Extensional Collapse Driven by Delamination in Central Tibet Prior to India‐Asia Collision - Yao Xiao; Xi Jun Liu; Hao Wu; Min Liu; Hai Yong Liu; Yu Jia Song; Fei Liu (Geochemistry, Geophysics, Geosystems, 2025)
Abstract A diverse range of dikes in the western Lhasa–Qiangtang collision zone provides constraints on the evolution of post‐collisional tectonomagmatic processes and the growth of the Tibetan Plateau. We report geochronological, geochemical, and Sr–Nd–Hf isotopic data for granitic dikes in the Rebang area of the Northern Lhasa Block, northern Tibet. Zircon U‐Pb dating of the granitic dikes reveals abundant inherited zircons with ages ranging from 1869 to 98.8 Ma, and the youngest age groups (83.9–82.0 Ma) indicate that they formed during the Late Cretaceous. The granitic dikes are characterized by high Sr and low Y contents and high Sr/Y ratios, and they have adakitic geochemical affinities and variable zircon εHf(t) (−6.01 to +9.82) and whole‐rock εNd(t) (−0.55 to +1.43) values. These features, together with the high Mg# values, suggest that the Rebang granitic dikes are derived by partial melting of thickened juvenile lower crust with variable degrees of contamination by mantle peridotite. The co‐occurrence of widely distributed dikes and thick‐bedded terrestrial molasses in the Late Cretaceous suggested that the central Tibet underwent post‐collisional extensional collapse, which was triggered by lithospheric delamination. We favor that isostatic rebound in response to delamination induces rapid surface uplifting and gravitational collapse in the Lhasa–Qiangtang collision zone. Additionally, our research proposes that the post‐collision extensional collapse in the Late Cretaceous plays an important role in the vertical growth of the Tibetan Plateau.